Regulation of Bud Rest in Tubers of Potato, Solanum tuberosum L: VII. Effect of Abscisic and Gibberellic Acids on Nucleic Acid Synthesis in Excised Buds - Shih, C. Y. (1970)
The effect of gibberellin A(3) (10(−4)m) and abscisic acid (10(−4)m), applied separately and together, on incorporation of (3)H-thymidine and (3)H-uridine into DNA and RNA of buds from freshly harvested potatoes was investigated. In some treatments apical buds in intact tubers were treated three times daily for 3 days with test solution before the buds were excised and treated an additional 12 hours in Petri dishes. In other treatments, untreated buds were excised and treated 12 hours. Irrespective of length of treatment, gibberellin A(3) slightly promoted synthesis of DNA and RNA, and abscisic acid essentially blocked such synthesis, in both the presence and absence of gibberellin A(3).